Serotonin transporter gene polymorphisms and depressive symptoms in patients with chronic obstructive pulmonary disease. (4th May 2021) - Yohannes, Abebaw Mengistu; Kohen, Ruth; Nguyen, Huong Q.; Pike, Kenneth C.; Borson, Soo; Fan, Vincent S.
ABSTRACT: Background : We examined the relationship between polymorphisms in the promoter region of the serotonin transport (SERT) gene (5-HTTLPR, short 'S' and long 'L' alleles) and in intron 2 variable number tandem repeat (STin2VNTR, 9, 10, or 12-repeat alleles) with depression or anxiety in patients with COPD. Methods : 302 patients with moderate to severe COPD participated in SERT study. History and number of prior depressive episodes were measured using the Structured Clinical Interview for Depression; Hospital Anxiety Depression Scale (HAD) depression ≥8 or a Patient Health Questionnaire-9 (PHQ-9) >, 10. Results : 240 (80%) male sample had a mean age of 68.0 years. Current depression was 22% (HAD) or 21% (PHQ-9), anxiety was 25% (HAD), and suicidal ideation (6%). 5-HTTLPR or STin2 VNTR genotypes were not associated with current depressive or anxiety symptoms. The mean number of prior depressive episodes was higher for patients with the 5-HTTLPR genotype S/S or S/L compared with L/L (4.4 ± 6.1; 5.3 ± 6.8; 4.0 ± 6.1, p < 0.001) and with STin2VNTR high-risk genotype (9/12 or 12/12), medium risk (9/10 or 10/12) compared to low risk (10/10) genotypes (5.1 ± 6.8; 4.9 ± 6.7; 2.7 ± 4.5, p < 0.001). Conclusions : SERT 5-HTTLPR and STin2-VNTR polymorphisms were not associated with current depressive and anxiety symptoms, but the high-risk STin2-VNTR genotypes and S/L were associated with the number of prior depressive episodes.